Migrating PBT TOEFL to iBT TOEFL: Opportunities and Challenges of Test Taker - Kiki Noventri Hermawanto; Ani Susanti (Universitas Islam Negeri Palopo, 2025)
In this era of globalization English proficiency test used as an indicator and requirement for student to go study abroad or get scholarship. PBT old service of proficiency test already stop and replaced with IBT test these phenomena to be issues that student faced now. This research aimed to determine the opportunities and challenges that’s Test Taker face. In this research, the researcher used qualitative research collects, analyzes, and interprets comprehensive narrative and visual data to gain insights into a particular phenomenon of interest. This Study research literature documents, the literature provides several steps to incorporate environmental variables in the efﬁciency estimation. Limitations associated with predictive validity studies, the scope of this study on the EFL Student as Test taker point of view. The focus of this study is to identify the opportunity and the obstacle that faced by EFL Student as test taker during the migration of PBT to iBT. The research that discusses about the opportunity and challenges related migration PBT TOEFL to iBT TOEFL still limited. In this case researcher will did this study to fill the gap of previews study.